Accuracy of the 2017 international recommendations for clinicians who interpret adolescent athletes' ECGs: a cohort study of 11 168 British white and black soccer players. Issue 12 (5th July 2019) - Malhotra, Aneil; Dhutia, Harshil; Yeo, Tee-Joo; Finocchiaro, Gherardo; Gati, Sabiha; Bulleros, Paulo; Fanton, Zephyr; Papatheodorou, Efstathios; Miles, Chris; Keteepe-Arachi, Tracey; Basu, Joyee; Parry-Williams, Gemma; et al.
Abstract : Aim: To investigate the accuracy of the recently published international recommendations for ECG interpretation in young athletes in a large cohort of white and black adolescent soccer players. Methods: 11 168 soccer players (mean age 16.4±1.2 years) were evaluated with a health questionnaire, ECG and echocardiogram; 10 581 (95%) of the players were male and 10 163 (91%) were white. ECGs were retrospectively analysed according to (1) the 2010 European Society of Cardiology (ESC) recommendations, (2) Seattle criteria, (3) refined criteria and (4) the international recommendations for ECG interpretation in young athletes. Results: The ESC recommendations resulted in a higher number of abnormal ECGs compared with the Seattle, refined and international criteria (13.2%, 4.3%, 2.9% and 1.8%, respectively). All four criteria were associated with a higher prevalence of abnormal ECGs in black athletes compared with white athletes (ESC: 16.2% vs 12.9%; Seattle: 5.9% vs 4.2%; refined: 3.8% vs 2.8%; international 3.6% vs 1.6%; p<0.001 each). Compared with ESC recommendations, the Seattle, refined and international criteria identified a lower number of abnormal ECGs—by 67%, 78% and 86%, respectively. All four criteria identified 36 (86%) of 42 athletes with serious cardiac pathology. Compared with ESC recommendations, the Seattle criteria improved specificity from 87% to 96% in white athletes and 84% to 94% in black athletes. The international recommendations demonstrated the highest specificity for white (99%) and black (97%) athletes and a sensitivity of 86%. Conclusions: The 2017 international recommendations for ECG interpretation in young athletes can be applied to adolescent athletes to detect serious cardiac disease. These recommendations perform more effectively than previous ECG criteria in both white and black adolescent soccer players.